PENGEMBANGAN MEDIA PEMBELAJARAN HAJI APP PADA MATA PELAJARAN FIQIH KELAS V DI MI TAHFIDZ AL-ASYHAR MADYOPURO MALANG - Istidamatul Iffah; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Learning media is everything that is used to convey information between teachers and students in understanding the material so that learning is more effective and students are able to gain knowledge, sklills, and attitudes. The use of learning media is to facilitate the teacher in delivering a material that is considered complicated and needs an explanation. One of the learning media is the Hajj App. it is a media in the form of a software application that designed to reseamble one of the WhatsApp smartphone application. This media contains Fiqh material about Hajj in the 5th grade of madrasah ibtidaiyah. In addition, this media complemented by learning videos. The focus of this media development research is (1) how the development of the Hajj App media as one of the media in learning Fiqh in the 5th grade in MI Tahfidz Al-Asyhar Madyopuro Malang, and (2) how the effectiveness of the application of learning media Hajj App in learning Fiqh in the 5th grade in MI Tahfidz Al-Asyhar Madyopuro Malang. The research method used by the developer is the ADDIE Research and Development model. The result of this study indicate that the media Hajj App is effectively used in Fiqh learning in the 5th grade which is showed by an increase in the average value obtained from the pretest with an average value of 57,8 and a post-test score of 86,8. From the result of this type of research development shows that the Hajj App learning media is quite effective to use in learning Fiqh.Keywords: Development, Learning media, Hajj App.